Aspek Yuridis Jual Beli Surat Keterangan Sakit melalui E-Commerce - Dinda Dinanti; Muthia Sakti (Universitas Medan Area, 2020)
In Indonesia, the development of services to produce fake documents that are in demand are sought after by the general public. One of them is buying and selling fake sick letters. At the research stage, the objective is to find out the responsibility of the perpetrators of the crime and efforts to counter the falsification of the sick letters which are traded through e-commerce. The juridical normative approach method emphasizes norms or rules so that the problem will be reviewed and analyzed with applicable legal guidelines and relating to the sale and purchase of fake sick letters through e-commerce in Indonesia. The crime of falsifying a sick letter being traded has entered the realm of criminal fraud. Which, has been regulated in Article 378 of the Criminal Code with a maximum imprisonment of 4 years and ITE Law Article 28 paragraph 1 threat of a maximum imprisonment of 6 years and / or a maximum fine of Rp 1,000,000,000. Efforts to overcome it through support from all elements. Even the public awareness of the harm caused when using these fake letters. Law enforcers cracked down on those who carried out the sale and purchase of the letter so that no one would dare to try to buy and sell the fake sick letter again.